Solve G(x) for the given domain.
G(x) = 3x 2 - 2x - 1
G(6) =

G(x) = 3x^2 - 2x - 1 G(6) = 3(6^2) - 2(6) - 1 = 108 - 12 - 1 = 95

Question

Asked 3/6/2014 11:10:12 AM

Updated 8/19/2014 11:50:03 PM

1 Answer/Comment

Rating

3

G(x) = 3x^2 - 2x - 1

G(6) = 3(6^2) - 2(6) - 1 = 108 - 12 - 1 = 95

G(6) = 3(6^2) - 2(6) - 1 = 108 - 12 - 1 = 95

Added 8/19/2014 11:50:03 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [8/19/2014 11:51:48 PM]

Solve G(x) for the given domain.
G(x) = 3x 2 - 2x - 1
G(a + b) =
**Weegy:** x = 27/4 **User:** Solve F(x) for the given domain.
F(x) = x 2+ 3x - 2
F(a) =
**Weegy:** x = 27/4 (More)

Question

Expert Answered

Updated 8/19/2014 11:52:20 PM

1 Answer/Comment

G(x) = 3x^2 - 2x - 1

G(a + b) = 3(a + b)^2 - 2(a + b) - 1

= 3a^2 + 6ab + 3b^2 - 2a - 2b - 1

G(a + b) = 3(a + b)^2 - 2(a + b) - 1

= 3a^2 + 6ab + 3b^2 - 2a - 2b - 1

Added 8/19/2014 11:52:20 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/19/2014 11:54:21 PM]

Solve F(x) for the given domain.
F(x) = x 2+ 3x - 2
F(a) =

Question

Not Answered

Updated 8/19/2014 11:50:50 PM

1 Answer/Comment

Solve F(x) for the given domain.
F(x) = x 2 + 3x - 2
F(-1) =
**Weegy:** (3x-2) squared is 9x^2 - 12x + 4. **User:** Solve F(x) for the given domain.
F(x) = x 2 + 3x - 2
F(-1) =
(More)

Question

Not Answered

Updated 8/19/2014 11:55:12 PM

1 Answer/Comment

Solve F(x) for the given domain.
F(x) = x 2 + 3x - 2
F(1) =
**Weegy:** 3x - 5 = 16; 3x = 21; x = 7. (More)

Question

Expert Answered

Updated 8/19/2014 11:53:05 PM

1 Answer/Comment

F(x) = x^2 + 3x - 2

F(1) = 1^2 + 3(1) - 2 = 1 + 3 - 2 = 2

F(1) = 1^2 + 3(1) - 2 = 1 + 3 - 2 = 2

Added 8/19/2014 11:53:05 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/19/2014 11:54:00 PM]

27,959,552

questions answered

There are no comments.